2017
DOI: 10.1371/journal.pone.0176594
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive learning of opposing unimanual motor tasks using the right arm followed by the left arm causes intermanual interference

Abstract: Intermanual transfer (motor memory generalization across arms) and motor memory interference (impairment of retest performance in consecutive motor learning) are well-investigated motor learning phenomena. However, the interplay of these phenomena remains elusive, i.e., whether intermanual interference occurs when two unimanual tasks are consecutively learned using different arms. Here, we examine intermanual interference when subjects consecutively adapt their right and left arm movements to novel dynamics. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(74 reference statements)
3
3
1
Order By: Relevance
“…This explains the initially poorer Transfer performance of all the groups compared to their initial Training and Posttest performance. This suggests the generalization did not take place in an extrinsic force-field transformation, but through intrinsic, mirror symmetric coordinates, which contradicts previous findings 36 . Paradoxically, we did not find an even greater decrease in initial Transfer performance in the Random groups, as would be expected for a more consolidated intrinsic representation in this group, which gives rise to predicting a force field in the opposite (wrong) direction during Transfer.…”
Section: Discussioncontrasting
confidence: 84%
“…This explains the initially poorer Transfer performance of all the groups compared to their initial Training and Posttest performance. This suggests the generalization did not take place in an extrinsic force-field transformation, but through intrinsic, mirror symmetric coordinates, which contradicts previous findings 36 . Paradoxically, we did not find an even greater decrease in initial Transfer performance in the Random groups, as would be expected for a more consolidated intrinsic representation in this group, which gives rise to predicting a force field in the opposite (wrong) direction during Transfer.…”
Section: Discussioncontrasting
confidence: 84%
“…Thus, there was no opportunity for complete adaptation with one limb before learning with the other limb ensued, which may be essential for interference to be seen. In line with this thought, Stockinger et al (2017) very recently demonstrated interference when the left arm was exposed to a force-field B following substantial adaptation of the right arm to an opposite force-field A. We also noted significant interference once subjects had undergone complete adaptation to the rotation, suggesting that substantial learning with the two arms may be essential to reveal interference.…”
Section: Discussionsupporting
confidence: 80%
“…While our results appear similar to those of Stockinger et al (2017), important differences between the findings exist. Most crucial among these is Stockinger and colleagues’ finding that the learning of B produced a deterioration of ~68% of the prior memory of A, while a control group that did not learn B showed a decrement of only about 15%.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This 481 suggest the generalization did not take place in extrinsic force field transformation but rather in intrinsic, 482 mirror symmetric coordinates, that is, perturbation was expected to come from right on the right hand and 483 from left on the left hand. This agrees with the literature (Shadmehr and Mussa-Ivaldi, 1994) but contradicts 484 the preference of extrinsic coordinates in other studies (Malfait and Ostry, 2004;Stockinger et al, 2017). 485…”
Section: Performance 478supporting
confidence: 83%